2019
DOI: 10.1038/s41419-019-1519-z
|View full text |Cite
|
Sign up to set email alerts
|

TAZ sensitizes EGFR wild-type non-small-cell lung cancer to gefitinib by promoting amphiregulin transcription

Abstract: Comparatively less toxic and more tolerated, epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) are recommendable for advanced non-small-cell lung cancer (NSCLC) patients with EGFR-sensitive mutations. Some EGFR wild-type patients with specific biomarkers also show a response to the drug. TAZ is an oncogene closely associated with the therapeutic effect of EGFR-TKIs. However, this association remains to be clarified. This study aimed to clarify the mechanism through which TAZ sensitizes EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
(39 reference statements)
1
21
0
Order By: Relevance
“…Recently, a systematic profiling of 9,125 tumor samples revealed a widespread dysregulation of Hippo pathway components in multiple human cancer types [ 31 ] The Hippo pathway integrates multiple signals to regulate the activity of core transcriptional coactivators YAP/TAZ, which directly or indirectly control multiple cancer hallmarks, including proliferation, survival, evading growth suppressors, reprogramming energy metabolism, angiogenesis, invasion and metastasis, and cancer stem cells, as well as inflammation and immunosuppression [ 31 ]. Our previous research found that TAZ was an oncogene closely associated with the therapeutic effect of cisplatin [ 32 ] and EGFR-TKIs [ 33 , 34 ] in lung adenocarcinoma. However, the role of YAP in lung adenocarcinoma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic profiling of 9,125 tumor samples revealed a widespread dysregulation of Hippo pathway components in multiple human cancer types [ 31 ] The Hippo pathway integrates multiple signals to regulate the activity of core transcriptional coactivators YAP/TAZ, which directly or indirectly control multiple cancer hallmarks, including proliferation, survival, evading growth suppressors, reprogramming energy metabolism, angiogenesis, invasion and metastasis, and cancer stem cells, as well as inflammation and immunosuppression [ 31 ]. Our previous research found that TAZ was an oncogene closely associated with the therapeutic effect of cisplatin [ 32 ] and EGFR-TKIs [ 33 , 34 ] in lung adenocarcinoma. However, the role of YAP in lung adenocarcinoma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppression [30]. Our previous research found that TAZ was an oncogene closely associated with the therapeutic effect of cisplatin [31] and EGFR-TKIs [32,33] in lung adenocarcinoma. However, the role of YAP in lung adenocarcinoma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, TAZ has been reported to be involved in VEGF-induced endothelial cell sprouting [ 54 ]. In addition, TAZ also enhances angiogenesis in EGFR wild-type non-small cell lung cancer cells [ 55 ]. According to these findings, we further evaluated the angiogenesis-inducing ability of conditioned medium acquired from control or TAZ-depleted cancer cells, and the results indicated TAZ has a key role in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%